Mental health: a stigma and neglected public health issue and time to break the barrier - Choudhary, Aditya; Jasrotia, Aakriti; Kumar, Abhishek (International Journal Of Community Medicine And Public Health, 2024)
Global mental health, impacting over a billion individuals, is addressed by the World Health Organization’s (WHO) 2023 special initiative for mental health, targeting accessible community-based care for 100 million people. The complexity of mental health dynamics, influenced by diverse factors, shapes an individual’s position on the continuum. Depression and suicide rates highlight the global crisis, with 970 million affected in 2019. India grapples with a treatment gap and economic implications, exacerbated by mental health stigma. Neglected in public health agendas, mental health imposes a significant burden, necessitating targeted policies and interventions. Breaking barriers requires collective efforts, including celebrity advocacy, organizational initiatives, and public education. Global interventions focus on suicide prevention through access restriction and responsible media reporting. Child and adolescent mental health necessitate policies promoting well-being and caregiver support, as seen in India’s Mental Healthcare Act of 2017. In conclusion, global mental health, a priority, faces persistent barriers, particularly stigma. Urgent action is needed to integrate mental health into broader public health strategies, dismantle discriminatory practices, and ensure equitable access to care for a future prioritizing universal well-being.